1995
DOI: 10.1017/s0043174500080796
|View full text |Cite
|
Sign up to set email alerts
|

Picloram Uptake, Translocation, and Efficacy in Relation to Water Status of Russian Knapweed (Acroptilon repens)

Abstract: Picloram uptake, translocation, and efficacy were studied using greenhouse-grown Russian knapweed plants. Uptake of14C-picloram, applied as discrete droplets to adaxial leaf surfaces of well-watered plants, averaged less than 10% of that applied. Most uptake occurred within 30 min of application. Uptake increased linearly with external picloram concentrations from 6.2 to 74.5 mM and was proportional to picloram concentration. Only about 10% of absorbed picloram was translocated out of the treated leaf of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Morrison et al . () measured no difference in picloram uptake but translocation was reduced with moisture stress, resulting in lower efficacy on Acoptilon repens . In contrast, the efficacy of fluroxypyr did not differ between the moist and the dry soils for Amaranthus palmerii , but it did differ for Kochia scoparia (Lubbers et al .…”
Section: Discussionmentioning
confidence: 94%
“…Morrison et al . () measured no difference in picloram uptake but translocation was reduced with moisture stress, resulting in lower efficacy on Acoptilon repens . In contrast, the efficacy of fluroxypyr did not differ between the moist and the dry soils for Amaranthus palmerii , but it did differ for Kochia scoparia (Lubbers et al .…”
Section: Discussionmentioning
confidence: 94%
“…The impact of water stress on herbicide translocation has been documented. Morrison et al (1995) reported on reduced herbicide translocation and poor control of Russian knapweed as a result of water stress.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental factors play a critical role in herbicide performance (Kudsk, ). A deficit in soil moisture can cause a significant reduction in herbicide efficacy (Coupland, ; Morrison et al ., ; Roche et al ., ) if target plants are water‐stressed prior to the time of application. Cool temperatures and low‐light intensity are also important factors, but less so than water stress (Coupland, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant vigour before and during treatment is an important factor affecting herbicide efficacy (Riethmuller‐Haage et al ., ). The efficacy of chemical control can also be compromised if target weeds are under moisture (Morrison et al ., ) or disease‐related stress (Vitelli & Madigan, ). In this study, it was important to know whether chlorophyll values assisted in the detection of environmental stress.…”
Section: Methodsmentioning
confidence: 99%